Exploration of digital technologies in Higher Education: teacher’s perspectives - Rodrigues, Maria Rosário (2020)
This study was developed under an ERASMUS + KA2 project started in December 2018 and developed by four H.E. institutions. In a first stage, it aims to understand the H.E. teachers learning environment, the access of teachers to technology, their perceptions and use of digital resources for teaching and learning. With this aim, a survey was carried out to teachers of higher education in Germany, Poland, Portugal and Slovenia, with 88 replies being obtained. Data analysis shows the teachers' recognition of the growing importance of ICT, and also the lack of knowledge of some of these technologies.